Ética e comunicação de risco na transposição das águas do rio São Francisco - Becker, Michele Amorim (2011)
This research has as objective to analyze of which forms the risk communication can contribute for an ethical quarrel in relation to the waters transposition of the San Francisco River. To reach our goal, we list three specific purposes: systemize Environmental Impact Report (RIMA) information related to the risks and social and environmental impacts caused by the Integration project of the San Francisco River with hydrographic basins of the northern northeast; to verify as sergipana press has located itself in relation to the transposition, by means of analysis of the journalistic speeches tied in Correio de Sergipe, Jornal da Cidade and Cinform periodicals, in the period from 2004 to 2007; identify information types and/or distortions presents in the analyzed journalistic speeches. This research itself uses of the structuralist method; it still has had a descriptive character, with primary and secondary document analysis. The study itself consists of bibliographical research on the theoretical beddings concerning the relation of the man with the nature, over all from modern authors, as Hobbes (2002) and Rousseau (1989, 1999), and contemporaries as Jonas (2006). To understand ourselves the environmental problematic in the present time, It became necessary to study the social construction of the risk , while factor that can contribute for the different threat perceptions and, therefore, to modify the exposition probability to the danger conditions. We list works by Habermas (2001, 2003) to think a communication based on the ethics about the speech. As for the documents research the information contained in the RIMA about risks and social and environmental impacts related to the transposition had been systemized. The journalistic speeches had been selected from its statements. In our analysis, we attempt to identify, at first, the study of meanings and the mapping of voices , so that we can employ discourse analysis do get to the discursive forms. We hope that the results obtained from this research can strengthen interdisciplinary academic debates, specially regarding the contributions of risk communication for an ethical discussion concerning the appropriate use of water, whether in the area of the São Francisco or those of other rivers in Sergipe. We may also expect the employ of risk communication in future environmental projects to stimulate the practice of transparency in the access to information, so as to make the dialogue between all concerned parts possible, as well as contributing to effective public participation in decision processes.